Моделювання руху поширення поверхневих плазмон-поляритонів у чотирьохканальному розгалужувачі з використанням MATLAB - Юрченко, В. М.; Чубукін, О. С. (ХНУРЕ, 2025)
The excitation and propagation of surface plasmonic polaritons (SPs) are important topics in solid-state physics and optics due to their significant potential in applications such as sensing, photonics, and nanotechnology. In this paper, we investigate the propagation of PPPs in a four-channel splitter using numerical simulations in MATLAB. The results demonstrate the dependence of the PPP propagation distance on the PPP wavelength and on the PPP frequency, which provides insight into the efficiency of multichannel plasma structures.
Keywords: плазмон-поляритон; MATLAB